A ML29 reassortant virus protects guinea pigs against a distantly related Nigerian strain of Lassa virus and can provide sterilizing immunity - Carrion, Ricardo; Patterson, Jean L.; Johnson, Curtis; Gonzales, Monica; Moreira, Carmen R.; Ticer, Anysha; Brasky, Kathleen; Hubbard, Gene B.; Moshkoff, Dmitry; Zapata, Juan; Salvato, Maria S.; Lukashevich, Igor S. (Vaccine, 2007)
Lassa virus (LASV) is responsible for the deaths of thousands of people in West Africa annually. Genetic diversity among LASV strains is the highest among the Arenaviridae and represents a great challenge for vaccine development. Guinea pigs vaccinated with a ML29 reassortant vaccine experienced sterilizing immunity and complete protection when challenged on day 30 either with homologous virus or with the distantly related Nigerian isolate. Simultaneous vaccination–challenge or challenge on day 2 after vaccination also protected 60–100% of the animals against both strains, but without sterilizing immunity. These results indicate that simultaneous replication of ML29 and LASV attenuates the virulence of LASV infection.